Refinements of Jensen’s inequality for convex functions on the co-ordinates in a rectangle from the plane - Khan, M. Adil; Ali, T.; Kilicman, Adem; Din, Q. (Faculty of Sciences and Mathematics, University of Nis, 2016)
In this paper our aim is to give refinements of Jensen’s type inequalities for the convex function defined on the co-ordinates of the bidimensional interval in the plane.